PERAN KELUARGA DALAM PELAKSANAAN ASIMILASI NARAPIDANA DI LEMBAGA PEMASYARAKATAN - Andi Muhammad Alifsa Mahendra; Mitro Subroto (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2022)
An inmate who is sentenced to a correctional facility is certainly faced with a pressure to deal with the problems he is currently facing, whether it is very high stress that will endanger the individual's physical and mental condition or the worst possibility, namely ending his life. The status of changing into a prisoner is the hardest thing to be separated from the family. The house assimilation policy is one of the goals in bringing prisoners closer to society, the family is one of the keys in implementing this program. Changing someone into a prisoner is not an easy thing, so it takes the support of a family who is willing to accept it again. This support is very meaningful in minimizing psychological disorders because being far from the closest people makes prisoners vulnerable to this. This situation is exacerbated by the existence of negative stigma from the community regarding the existence of prisoners, namely people who are considered to have a negative influence and can harm the community. With such circumstances, it is necessary to have an encouragement that plays a role in preventing, overcoming, and avoiding negative impacts that can harm themselves or others where prisoners feel that they have someone who loves, cares, and respects themselves so that they can reduce anxiety or stress that is more intense. . The house assimilation policy is one of the goals in bringing prisoners closer to society, the family is one of the keys in implementing this program.